Pengaruh Perbandingan Terigu dan Tepung Sukun (Artocarpus altilis) Terhadap Sifat Fisiko-Kimia dan Sensoris Bolu Kukus - Surachman, Ronald; Kencana Putra, I Nengah; Sri Wiadnyani, Anak agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
In general, the raw ingredients for making steamed sponge is wheat flour, but nowadays it can be mixed with breadfruit flour to reduce the use of wheat flour. This study aimed to determine the effect of the comparison of wheat flour and breadfruit flour (Artocarpus altilis) on physico-chemical and sensory properties of steamed sponge cake and find out the comparison of wheat flour and breadfruit flour to obtain the best physico-chemical and sensory properties of steamed sponge cake. The experimental design used was Completely Randomized Design with the comparison treatment. The design used in this study was a Completely Randomized Design (CRD) with the treatment of the amount of wheat flour and breadfruit flour (100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40% and 50%:50%). All treatments were repeated three times, resulting in 18 experimental units. The data obtained were analyzed with Analysis of Variance and if the treatment had a significant effect, then continued with the Duncan Multiple Range Test. The results showed that the addition of breadfruit flour had a significant effect on water content, ash content, protein content, fat content, crude fiber content, carbohydrate content, swelling power, scoring test for color, smell, texture, taste, hedonic test for taste and overall acceptance. A comparison of 70% wheat flour and 30% breadfruit flour produces steamed sponge cake with the best physico-chemical and sensory properties with the criteria of 34.04% moisture content, 0.84% ash content, 6.17% protein content, 3.73% fat content, 55.21% carbohydrate content, 3.53% crude fiber content, 65.80% swelling power and sensory properties of cream color and slightly like, the smell of breadfruit is weak and slightly like, the texture is slightly soft and slightly like, breadfruit taste is weak and slightly like, and overall acceptance is slightly like.